2019
DOI: 10.3390/plants8120528
|View full text |Cite
|
Sign up to set email alerts
|

Fly-Ash Pollution Modulates Growth, Biochemical Attributes, Antioxidant Activity and Gene Expression in Pithecellobium Dulce (Roxb) Benth

Abstract: This study investigates the effect of fly ash (FA) on the Pithecellobium dulce (Roxb) Benth. trees growing at three different locations. FA stress caused significant changes in different leaf attributes like sugar, protein contents, photosynthetic pigments, nitrate content and nitrate reductase activity in foliar tissues of plants growing at a highly contaminated site, as compared to a low-pollution site. Lower rates of stomatal conductance (SC) were observed in P. dulce leaves under fly ash stress conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The accumulation of ROS induced by stressful conditions can lead to nucleic acid injury, enzyme inhibition, and eventually, the death of cells in plants (Imran et al, 2021). The activities of antioxidant enzymes increases during detoxi cation in plants under stressful conditions (Hou et al, 2007;Qadir et al, 2019). Notably, SOD is considered the rst line of defense against ROS, as it decomposes O 2 •− to H 2 O 2 and O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ROS induced by stressful conditions can lead to nucleic acid injury, enzyme inhibition, and eventually, the death of cells in plants (Imran et al, 2021). The activities of antioxidant enzymes increases during detoxi cation in plants under stressful conditions (Hou et al, 2007;Qadir et al, 2019). Notably, SOD is considered the rst line of defense against ROS, as it decomposes O 2 •− to H 2 O 2 and O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…CL and after a 3-year restoration following further growth. Similarly,Qadir et al (2019) illustrate that Pithecellobium dulce can achieve good growth on FA-CL. It can induce FA-CL restoration due to an enhanced antioxidant mechanism against free radicals stress conditions.…”
mentioning
confidence: 87%
“…FA-CL containing heavy metals induces stress in leafy vegetables, and Singh et al (2008) have observed heavy metalsinduced stress in Beta vulgaris. Therefore, the IPS for restoring FA-CL should reflect climate adaptive and phytoremediation potential (Qadir et al, 2019). Gajic et al (2018) illustrated that phytoremediation potentials are based on four criteria: phytostabilization (P-S), phytoextraction (P-X), phytodegradation (P-D) and rhizo-degradation (R-D).…”
Section: Identifying the Potential Of Indigenous Plant Species And Understanding Local Demandsmentioning
confidence: 99%
“…In several studies, the response of antioxidants has been observed to compete against oxidative stress due to the overproduction of ROS. FA enriched with metals and metalloids like Fe, Ni, As, B, Se, Pb, Cr, Pb, Cu, and Cd are the alarms of toxicity, which not only pollute the environment but also result in oxidative stress with the production of ROS such as peroxide and superoxide radicals (Qadir et al, 2019). It creates oxidative stress by electron transfer and inhibition of metabolic reactions (Pandey et al, 2010).…”
Section: Antioxidant Responsesmentioning
confidence: 99%